2023
DOI: 10.1371/journal.pdig.0000249
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning to predict bacteriologic confirmation of Mycobacterium tuberculosis in infants and very young children

Abstract: Diagnosis of tuberculosis (TB) among young children (<5 years) is challenging due to the paucibacillary nature of clinical disease and clinical similarities to other childhood diseases. We used machine learning to develop accurate prediction models of microbial confirmation with simply defined and easily obtainable clinical, demographic, and radiologic factors. We evaluated eleven supervised machine learning models (using stepwise regression, regularized regression, decision tree, and support vector machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In contrast, other studies in the medical field that have achieved superior results have not only incorporated binary variables but have also integrated continuous variables obtained from laboratory tests and biometric measurements to assess patients' conditions [19,20,32,37]. An illustrative case from [21] involved the transformation of continuous data into binary values, but this approach also yielded unsatisfactory results. It is plausible that, in our case, the lack of relevant information and the use of subjective values to evaluate the health status of patients may have led to weaker associations between these characteristics and the occurrence of influenza.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other studies in the medical field that have achieved superior results have not only incorporated binary variables but have also integrated continuous variables obtained from laboratory tests and biometric measurements to assess patients' conditions [19,20,32,37]. An illustrative case from [21] involved the transformation of continuous data into binary values, but this approach also yielded unsatisfactory results. It is plausible that, in our case, the lack of relevant information and the use of subjective values to evaluate the health status of patients may have led to weaker associations between these characteristics and the occurrence of influenza.…”
Section: Resultsmentioning
confidence: 99%
“…It has employed ML models for the development of prediction performance. It has used a new dataset, and the result has shown that the prevailing mechanism has attained better values in accuracy metrics (Smith et al, 2023 ). Contrarily, the suggested model has diagnosed TB from real-world cough recordings and has incorporated the conventional ML models for better prediction.…”
Section: Literature Reviewmentioning
confidence: 99%